URGENSI PEMBELAJARAN HUMANIS DI SEKOLAH - Dudiyono (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
When we observe the learning process that occurs during this time, as if the meaning of learning in school has undergone a shift in orientation, learning in context, there is now a tendency to only obtain the values in terms of "numbers". So as if the outcome of the learning process just stopped on the series of numbers, but more than that how to row the numbers were nice it actualized in daily life through the daily attitude of learners humanist consistently. Humanist learning is a learning in which the learning process forward learners so that they have an awareness of the importance of life together despite different religious background, ethnicity, nationality, race, culture and economy. So that the learning process emphasizes how learners can be individuals that humanize and learners are able to develop her potential. Key Words: Humanist Learning, School